2015
DOI: 10.15406/ghoa.2015.02.00038
|View full text |Cite
|
Sign up to set email alerts
|

"Role of Psychosocial Factors on the Course of Inflammatory Bowel Disease and Associated Psychotherapeutic Approaches. A Fresh Perspective and Review"

Abstract: In this review article we seek to provide a fresh prospective on the role of psychosocial factors such as stress, anxiety, and depression, in the course of Inflammatory Bowel Diseases (IBD). IBD patients suffer from depression and anxiety at higher rates than the general population. Psychological stressors adversely affect the course of IBD through activation and possible dysfunction of the Brain-Gut-Axis. The mechanisms by which psychological factors increase mucosal inflammation, disrupt the intestinal barri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
(164 reference statements)
0
2
0
Order By: Relevance
“…Like anxiety and depression, exposure to stress is a major risk factor impacting IBD and is also linked to adverse patient outcomes, such as reduced QoL (Van de Star & Banan, 2015) and psychological well-being (Melinder et al, 2017; van der Sloot et al, 2020). In a recent systematic review involving 13 of 18 prospective studies ( n = 1,283), Cámara et al (2009) concluded that stress was linked to exacerbating IBD activity.…”
Section: Introductionmentioning
confidence: 99%
“…Like anxiety and depression, exposure to stress is a major risk factor impacting IBD and is also linked to adverse patient outcomes, such as reduced QoL (Van de Star & Banan, 2015) and psychological well-being (Melinder et al, 2017; van der Sloot et al, 2020). In a recent systematic review involving 13 of 18 prospective studies ( n = 1,283), Cámara et al (2009) concluded that stress was linked to exacerbating IBD activity.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the health-related quality of life (HRQOL) in patients suffering from UC is lower compared to the healthy individuals (8,9). Many studies have shown that the medical treatment (corticosteroids and immunosuppressive-drugs) (8), extra-intestinal manifestations (10) and employment status (11) are among the factors which reduce the HRQOL of patients suffering from UC (12,13). In addition, there are contradictory data in regard to the effect of therapeutic regimens of UC on HRQOL.…”
Section: Introductionmentioning
confidence: 99%